REASONS FOR BURNOUT AND POSSIBILITIES FOR REHABILITATION FOR - Gyrnik, A.N.; Bogdanov, S.A.; Donets, Yu.V.; Chernobrovkina, V.A.; Romanenko, L.D.; Solovyova, V.V. (Modern Psychology, 2019)
The paper examines the main reasons for burnout among the educators who work close to the contact line (0-15 km) between the Ukrainian Army and the separatist detachments, as well as the results of the rehabilitation for the teachers. The research was carried out in three stages and relied on the individual interviews, focus group interviews, and professional stress questionnaire. The same high burnout level among the educators who work in the contact zone and those who work at the 60 km. distance from the zone of military operations was revealed. The study established considerable emotional burnout level reduction and depersonalization of teachers after the emotional burnout coping training and subsequent nine month practical classes. The significant role in burnout overcoming was played by the change of teachers' sence of social wellbeing.
Keywords: mental health; mental stress; burnout; sense of social well-being; teacher training